2018
DOI: 10.1186/s12967-018-1479-6
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of TLR4 signaling in intermittent hypoxia-mediated atherosclerosis progression

Abstract: BackgroundIntermittent hypoxia (IH), a typical character of obstructive sleep apnea (OSA), is related to atherogenesis. However, the role of IH on atherosclerosis (AS) progression and the mechanisms involved remains poorly understood.MethodsIn the present study, high-fat fed ApoE−/− mice were treated with recombinant shRNA-TLR4 lentivirus and exposed to IH. Atherosclerotic lesions on the en face aorta and cross-sections of aortic root were examined by Oil-Red O staining. The content of lipids and collagen of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 31 publications
(43 reference statements)
1
27
0
1
Order By: Relevance
“…In human aortic SMC, LPS stimulates TLR4 signaling to promote the release of MCP-1, IL-1α, and IL-6 [ 53 ]. Contribution of TLR4 signaling in intermittent hypoxia-mediated atherosclerosis progression [ 54 ]. So TLR4 signaling maybe an ideal target for interfering in the AS progression.…”
Section: Atherosclerosis Related Inflammatory Signaling Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…In human aortic SMC, LPS stimulates TLR4 signaling to promote the release of MCP-1, IL-1α, and IL-6 [ 53 ]. Contribution of TLR4 signaling in intermittent hypoxia-mediated atherosclerosis progression [ 54 ]. So TLR4 signaling maybe an ideal target for interfering in the AS progression.…”
Section: Atherosclerosis Related Inflammatory Signaling Pathwaysmentioning
confidence: 99%
“…However, inhibition of NF-κB activation in macrophages causes a reduction of foam cell formation, anti-apoptosis, and anti-inflammation [ 58 ]. Triggering the activation of TLR4/NF-κB signaling and the downstream proinflammatory responses promotes the plaque growth and instability [ 54 ].…”
Section: Atherosclerosis Related Inflammatory Signaling Pathwaysmentioning
confidence: 99%
“…Serum collected from each mouse was centrifuged at 3000 rpm for 15 min and stored at − 80°C for further analysis. Blood biochemical tests to detect serum lipids (cholesterol, triglyceride, high density lipoprotein cholesterol, low density lipoprotein cholesterol, and free fatty acid) and blood glucose were performed as described in our previous report [18].…”
Section: Serum Biochemical Analysismentioning
confidence: 99%
“…TLRs, membrane-spanning proteins, have been implicated in the progression and development of many chronic diseases [15]. TLR4 has also been implicated in the development and progression of cardiovascular disease by inducing endothelial dysfunction [8, 10]. Study showed that TLR4 knockout led to marked reduction of aortic plaque area, decreased inflammation, and reduced oxidative damage [16].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a growing body of evidence has elucidated their role in regulating the inflammatory response and maintaining endothelial homeostasis [5]. TLR4, the first identified TLR, has also been implicated in the development and progression of cardiovascular disease [8, 9]. Several studies have reported a role of TLR4 in promoting ECs proliferation and neointima formation [10].…”
Section: Introductionmentioning
confidence: 99%